STRUKTUR FORMULA DALAM SYAIR LAGU DOLANAN ANAK-ANAK DI KABUPATEN JOMBANG (Kajian Struktur Naratif Albert B. Lord) - DAMARISWARA*, RIAN (Universitas Muhammadiyah Jember, 2016)
The lyries of Nursery Rymes in Jombang, Jember has its own typical characteristes compared to the other lyries of Nursery Rymes in other parts of Java. In Jombang, it has the natural laguage of Jombangan, that is the mixing of Mataraman dialect or Jogja/Solo and arek dialect or Surabaya.There has not been any study focused on the lyrics of Nursery Rymes in Java which was typically regional and case study based. The purpose of the study is to describe the stucture of the formula used in the lyrics of Jombang Nursery Rymes. The theory used is the narrative structure theory of Albert.B.Lord. The method of the study is qualitative. The nature of the study is using informant. The data is in the form of Jombang Nursery Rymes lyrics. The data colletion technig us applied are observation (participant observation) taping and recording, the resuets of the study show that (1) the formula of the lines comprised of the connection or interelationship based on the syntaxis on wordy, complete contruction and elypses, structure similarity, rymes, aliteration and subtitutions.(2) The formula of the lines comprises, the length of the lines, the patterns of the lines, the rymes of the lines.Key words: formula structure, nursery rymes.